Quality improvement of the medication system in a long-term care facility: a hybrid effectiveness-implementation study - Ana Ludmila Santos Plauska; Hágabo Mathyell Silva; Juliana de Oliveira Gomes Ramos; Cristiane de Paula Rezende; Mariana Martins Gonzaga do Nascimento (Geriatrics, Gerontology and Aging)
Objective: To describe the implementation of a quality improvement intervention for the medication system of a large not-for-profit long-term care facility (LTCF) and evaluate its effectiveness. Methods: A type 2 effectiveness-implementation hybrid longitudinal study was carried out. We first conducted a diagnosis of the existing medication system, which included the administration of a questionnaire to LTCF staff. Then, an individualized unit-dose dispensing system was implemented and the medication system’s flow was adjusted to the local reality. The effectiveness of the quality improvement intervention was assessed by comparing the following pre- and post-implementation factors: 1) time spent on each step of the medication system; 2) strengths and weaknesses observed. Results: The diagnosis demonstrated multiple points of failure in the medication system. However, the answers to the questionnaire ran counter to what was identified, indicating a lack of knowledge about patient safety. The quality improvement intervention was associated with the following improvements in the medication system: 1) reduction in the number of prescription transcriptions; 2) reduction of medication shortages; and 3) improvement of organization, dynamics, and traceability in distribution, preparation, and administration. An average reduction of 3 hours and 57 minutes in the time spent distributing, preparing, and administering medications was also identified. Conclusions: The quality improvement intervention was effective, increased the providers’ available time, and improved the safety of medication use in the LTCF.